Impact of comorbidities on overall survival in patients with chronic myeloid leukemia: results of the randomized CML Study IV - Saußele, Susanne; Krauß, Marie-Paloma; Hehlmann, Rüdiger; Proetel, Ulrike; Kalmanti, Lida; Hanfstein, Benjamin; Fabarius, Alice; Hofmann, Wolf-Karsten; Müller, Martin Christian (Blood, 2015)
We studied the influence of comorbidities on remission rate and overall survival (OS) in patients with chronic myeloid leukemia (CML). Participants of the CML Study IV, a randomized 5-arm trial designed to optimize imatinib therapy, were analyzed for comorbidities at diagnosis using the Charlson Comorbidity Index (CCI); 511 indexed comorbidities were reported in 1519 CML patients. Age was an additional risk factor in 863 patients. Resulting CCI scores were as follows: CCI 2, n = 589; CCI 3 or 4, n = 599; CCI 5 or 6, n = 229; and CCI ≥ 7, n = 102. No differences in cumulative incidences of accelerated phase, blast crisis, or remission rates were observed between patients in the different CCI groups. Higher CCI was significantly associated with lower OS probabilities. The 8-year OS probabilities were 93.6%, 89.4%, 77.6%, and 46.4% for patients with CCI 2, 3 to 4, 5 to 6, and ≥7, respectively. In multivariate analysis, CCI was the most powerful predictor of OS, which was still valid after removal of its age-related components. Comorbidities have no impact on treatment success but do have a negative effect on OS, indicating that survival of patients with CML is determined more by comorbidities than by CML itself. OS may therefore be inappropriate as an outcome measure for specific CML treatments. The trial was registered at www.clinicaltrials.gov as #NCT00055874.